Axonal mitochondria adjust in size depending on g‐ratio of surrounding myelin during homeostasis and advanced remyelination. Issue 3 (25th December 2020) - Ineichen, Benjamin V.; Zhu, Keying; Carlström, Karl E.
Abstract: Demyelinating pathology is common in many neurological diseases such as multiple sclerosis, stroke, and Alzheimer's disease and results in axonal energy deficiency, dysfunctional axonal propagation, and neurodegeneration. During myelin repair and also during myelin homeostasis, mutual regulative processes between axons and myelin sheaths are known to be essential. However, proficient tools are lacking to characterize axon‐myelin interdependence during (re)myelination. Thus, we herein investigated adaptions in myelin sheath g ‐ratio as a proxy for myelin thickness and axon metabolic status during homeostasis and myelin repair, by using axonal mitochondrial size as a proxy for axonal metabolic status. We found that axons with thinner myelin sheaths had larger axonal mitochondria; this was true for across different central nervous system tracts as well as across species, including humans. The link between myelin sheath thickness and mitochondrial size was temporarily absent during demyelination but reestablished during advanced remyelination, as shown in two commonly used animal models of toxic demyelination. By further exploring this association in mice with either genetically induced mitochondrial or myelin dysfunction, we show that axonal mitochondrial size adjusts in response to the thickness of the myelin sheath but not vice versa . This pinpoints the relevance of mitochondrial adaptation upon myelin repair and might open a new therapeutic window for remyelinating therapies. Abstract : Axonal mitochondrial size correlates with g ‐ratio during homeostasis in multiple species and during advanced remyelination. But not during early remyelination. Oligodendrocyte mitochondria function influence myelin thickness which influence axonal mitochondria size.